Towards an alternative spatial-based management approach for estuarine fisheries in South Africa, with a case study from the Sundays Estuary - Kramer, Rachel (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Estuaries are productive habitats and biologically important ecosystems which serve as juvenile nursery areas and feeding grounds for adults from a host of fish species. They are, however, threatened habitats, increasingly exposed to human disturbance and exploitation. The stocks of several South African estuary-dependent linefish species are now considered as either overexploited or collapsed. It is clear that their dependence on estuaries would warrant the inclusion of these ecosystems into marine reserve planning exercises. Since traditional management strategies (e.g. bag and size limit restrictions) have proven ineffective for estuarine fisheries, there is a need for alternative management measures, such as spatial and temporal restrictions, to ensure increased survival of juveniles and recovery of adult breeding populations. This thesis explored the potential for an ecosystem-based approach through the application of a rapid sustainability assessment technique, and a spatial-based management approach for an important fishery species, using conservation planning software. The Sundays Estuary, Eastern Cape, South Africa falls within the footprint of the Addo Elephant National Park, with a proposed expansion to include a marine protected area (MPA). However the estuaries resources were not considered during the planning of the proposed MPA. This study conducted an indicator-based sustainability assessment based on the principles of sustainable development. The results showed that present levels of exploitation, due to non-compliance and a lack of law enforcement are unsustainable. The sustainability of the Sundays Estuary had a low overall sustainability score of only 23.8%. With limited enforcement of estuarine fisheries regulations in South Africa, alternative management measures such as spatial regulations may provide a viable option forward. The sustainability of fishery resources depends on the comprehensive understanding of the fishery resource. Acoustic telemetry is a technique that has been widely adopted to infer habitat and area use patterns of fish species. The second component of this study made use of high resolution telemetry data collected on juvenile dusky kob Argyrosomus japonicus movements within the Sundays Estuary to conduct a scenario-based approach using Marxan conservation planning software. The best solution given by Marxan, in the form of a protected area for the conservation of juvenile A. japonicus in the Sundays Estuary was identified in the middle (starting 7km from the mouth) to the upper reaches (approximately 16km from the mouth) of the estuary, ultimately providing protection to tagged individuals for 61% of their time in the estuary. Although Marxan presented a best solution, the Sundays Estuary's small size and shape, and minimal features used, was too simplistic to be included into a Marxan analysis. However, new methods and tools to analyse and plan spatial-based management options at this scale are currently being developed. Using the Sundays Estuary as a case study, a decision tree was then developed as a protocol to assist management address the challenges of effective estuarine management depending on the unique biological and socio-economic characteristics of individual estuaries in South Africa.
Keywords: Uncatalogued